The Handbook of language emergence - MacWhinney, Brian; O'Grady, William (Chichester, West Sussex, [United Kingdom] Wiley Blackwell, 2015)
"This book explores the latest integrated theory for understanding human language. The authors focus on the ways in which the learning, processing, and structure of language emerge from a competing set of cognitive, communicative, and biological constraints. In addition, the book examine forces on widely divergent time scales, from instantaneous neurolinguistic processing to historical changes and language evolution. Key theoretical, empirical, and methodological issues are also addressed"-- Provided by publisher.
Table of Contents: Notes on Contributors -- Introduction: Basic Language Structures / Brian MacWhinney -- 1. The Emergence of Phonological Representation / Patricia Donegan -- 2. Capturing Gradience, Continuous Change, and Quasi-Regularity in Sound, Word, Phrase, and Meaning / Jay McClelland -- 3. The Emergence of Language Comprehension / Maryellen McDonald -- 4. Anaphora and the Case for Emergentism / William O'Grady -- 5. Morphological Emergence / Peter Racz, Janet Pierre-Humbert, Jennifer Hay, & Viktoria Papp -- 6. Metaphor and Emergentism / Zoltan Kovecses -- 7. Usage-based Language Learning / Nick Ellis, Matthew O'Donnell, & Ute Romer -- II. Language Change and Typology -- 8. Emergence at the Crosslinguistic Level: Attractor Dynamics in Language Change / Joan Bybee and Clayton Beckner -- 9. The Diachronic Genesis of Synchronic Syntax / Tom Givon -- 10. Typological Variation and Efficient Processing / John Hawkins -- 11. Word meanings across languages support efficient communication / Terry Regier, Charles Kemp, and Paul Kay -- III. Interactional Structures -- 12. Linguistic Emergence on the Ground - a Variationist Paradigm / Shana Poplack and Rena Torres Cacoullos -- 13. The Emergence of Sociophonetic Structure / Paul Foulkes and Jennifer Hay -- 14. An Emergentist Approach to Grammar / Paul Hopper -- 15. Common Ground / Eve Clark -- 16. The Role of Culture in the Emergence of Language / Dan Everett -- IV. Language Learning -- 17. Learnability / Alexander Clark -- 18. Perceptual Development and Statistical Learning / Erik Thiessen and Lucy Erickson -- 19. Language Emergence in Development - A Computational Perspective / Stewart McCauley, Padraic Monaghan, & Morten Christiansen -- 20. Perception and Production in Phonological Development / Marilyn Vihman -- 21. The Emergence of Gestures / Jordan Zlatev -- 22. A Constructivist Account of Child Language Acquisition / Ben Ambridge & Elena Lieven -- 23. Bilingualism as a Dynamic Process / Ping Li -- 24. Dynamic Systems and Language Development / Paul van Geert and Marjolijn Verspoor -- V. Language and the Brain -- 25. Models of Language Production in Aphasia / Gary Dell & Nathaniel Anderson -- 26. Formulaic Language in an Emergentist Framework / Diana Van Lanckner Sidtis -- 27. Language Evolution - An Emergentist Perspective / Michael Arbib.
Includes bibliographical references and index.
Keywords: Language and languages -- Origin; Linguistics